BRAIN DERIVED NEUROTROPHIC FACTOR (BDNF) PASCACEDERA KEPALA BERAT SEBAGAI FAKTOR PERAMALAN PERJALANAN PENYAKIT (Brain Derived Neurotrophic Factor (BDNF) as a Prognostic Factor in Severe Head Injury) - Ridha Dharmajaya (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Severe head Injury result in primary and secondary brain damage. The secondary brain damage produces a more worse effect thanthe primary one. Therefore, the process of the secondary brain damage should be prevented in order to obtain a maximum result ofpatient management. The difficulty is to make sure, whether the secondary brain damage is already very bad or, on the other hand, isstill in a positive condition, causing patient management to have a good result. The prognostic decision, is the most important thing inpatient management. The objective of this research was to find an accurate prognostic factor which is simple and non invasive for severehead injury for each time lapse, 24, 48, 72 and 120 hours after the brain damage which had caused the head injury. The installation ofan intracranial pressure (ICP) monitor for the first 24 hours, after the head injury, followed by taking a cerebrospinal fluid sample forBDNF examination at the first 24 hours, 48 hours, 72 hours and 120 hours as well. Enzyme Linked Immunosorbent Assay was used todetermine BDNF. Each subject was assessed by Glasgow Outcome Scale classification, three months after the injury. The result of thisresearch was that BDNF at 48 hours after head injury showed a significant difference (p < 0.05) between good and bad Glasgow OutcomeScale classification. Thus, it can be concluded that patients with an increase in BDNF (>6.16 pg/mL) 48 hours after head injury, mayhave a good prognosis.